Suprapubic catheterisation: a study of 1000 elective procedures. (10th April 2022) - Hobbs, Catherine; Howles, Sarah; Derry, Fadel; Reynard, John
Abstract : Objectives: To investigate the risks and long‐term outcomes of suprapubic catheter (SPC) insertion in a population predominantly with spinal cord injury. Materials and Methods: We used the theatre database at the National Spinal Injuries Centre in Stoke Mandeville Hospital to identify 1000 consecutive SPC insertions from 1998 to 2015. We retrospectively analysed all records for these patients. Results: Follow‐up ranged from 4 weeks to 16.45 years (median 3.3 years). Either cystoscopy‐guided suprapubic puncture (Lawrence Add‐a‐Cath trochar) or a direct incision onto a urethral sound (Lowsley retractor) followed by cystoscopy was used for 98% of insertions. Complications graded as Clavien–Dindo IIIb or higher occurred in 0.6% of patients. Return to theatre was necessary in 0.4%, including three laparotomies due to bleeding or misplacement of the catheter, but no bowel injuries occurred. One death occurred within 30 days due to pulmonary embolism. There were no significant differences in outcomes between insertion methods. Tolerance of long‐term suprapubic catheterisation was high, despite 59% of cases experiencing mostly minor complications. Tract losses during routine community change and variability in antibiotic prescribing highlighted areas for educational development which could improve patient outcomes. Conclusions: This study supports the view that the risk of major complications from SPC insertion is lower than previously reported. Minor complications related to the catheter are common in the long term but are generally well tolerated.